Can executives’ digital background develop the level of AI utilization in enterprises - Ruichao Yu; Linrong Wu; Guiying Li; Zixin Wang (PeerJ Computer Science)
Digital talent has emerged as a pivotal resource for advancing artificial intelligence (AI) within enterprises, and it constitutes a critical digital asset that firms prioritize in their AI development strategies, aiming to attract and retain such talent. To elucidate the interconnections and mechanisms linking the digital backgrounds of executives with the level of AI utilization in enterprises, this study undertakes an examination of the relationship between these two variables, drawing on a sample of Chinese A-share listed companies spanning from 2012 to 2022. The research findings are as follows: (1) The presence of a substantial number of executives with digital backgrounds within a company significantly enhances the development of AI utilization within the enterprise. (2) The influence of executives’ digital backgrounds on the level of AI utilization in enterprises is modulated through the enhancement of the enterprise’s total factor productivity. (3) Executives’ digital backgrounds elevate the level of AI utilization by bolstering their proficiency in applying digital technology. (4) Heterogeneity analysis, conducted based on the nature of enterprise property rights, geographical regions, and technological proficiency, reveals that the positive effect of executives’ digital backgrounds on AI utilization is more pronounced in private enterprises compared to state-owned enterprises. Regionally, the impact of executives’ digital backgrounds on AI utilization diminishes progressively from the eastern to the central and western regions. Robustness checks, including the substitution of key variables, model alteration, the application of the instrumental variable method, and the Heckman two-stage method, confirm the persistence of these findings. This article contributes to the understanding of the impact and pathways through which executives’ digital backgrounds influence AI utilization in enterprises against the backdrop of high-quality economic development. It enriches the scholarly discourse on executives’ digital backgrounds and AI utilization in enterprises, offering both theoretical support and practical insights for the advancement of AI within enterprises.